2011
DOI: 10.1111/j.1466-7657.2011.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of high‐fidelity simulation to nursing students' confidence and competence: a systematic review

Abstract: Background: High-fidelity simulation (HFS) has been proposed as a novel, supplemental teaching-learning strategy to enhance students' confidence and competence in nursing practice. Aim: To describe available evidence about the effects of HFS on students' confidence and competence within nursing educational programmes. Methods: A review of studies published between 2000 and 2011 was undertaken using the following databases: CINAHL, Proquest, MEDLINE, Science Direct, OVID and Chinese Academic Journal. The concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 26 publications
(43 reference statements)
2
70
1
7
Order By: Relevance
“…[29,30] Self-confidence is an important predictor for success in professional roles, job satisfaction, and career longevity, [13,14] all of which have implications for nursing faculty charged with educating new workforce entrants. Our results show that student's perceptions of their confidence in carrying out the eight practice competencies associated with generalist nursing practice set forth by the American Association of Colleges of Nursing, the National League for Nursing, and National Council of State Boards of Nursing significantly improved over time in the undergraduate program.…”
Section: Discussionmentioning
confidence: 99%
“…[29,30] Self-confidence is an important predictor for success in professional roles, job satisfaction, and career longevity, [13,14] all of which have implications for nursing faculty charged with educating new workforce entrants. Our results show that student's perceptions of their confidence in carrying out the eight practice competencies associated with generalist nursing practice set forth by the American Association of Colleges of Nursing, the National League for Nursing, and National Council of State Boards of Nursing significantly improved over time in the undergraduate program.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review on current empirical studies (between 2000 and 2011) indicated the high-fidelity simulation did enhance scores on knowledge and skill exams but provided a mixed contribution to self-confidence and competency [7,8] . Based on self-report surveys, many Chinese students perceived that simulation effectively improved their abilities in communication, team collaboration, clinical thinking, clinical judgment and problem solving [9,10] .…”
mentioning
confidence: 99%
“…Öğrencilerin simülasyon eğitimi ile kazandığı yeterlilik ve öz güvenin, klinikte/alanda gerçek bir durumla karşılaştığında göstereceği öz güven ve yeterlilik ile aynı olmayacağı ya da farklı olacağı belirtilmiştir. 20 Bu sistematik incelemenin aksine araştırmada eğitimciler, simülasyon eğitiminin öğ-renciye (beceriyi, öz güveni, kendini ifade etme yeteneğini, hızlı analitik ve eleştirel düşünme, kritik karar verme ve sorun çözme becerisini artırır vb. ), eğitimciye (klasik eğitime göre daha keyifli ve doyum vericidir, anlatımı kolaylaştırır, hastanın zarar görme riski azaldığı için eğitimci kendini gü-vende hisseder vb.)…”
Section: Discussionunclassified